Diagnosis of Distal Cholangiocarcinoma after the Removal of Choledocholithiasis - Yasuhiro Ito; Takeshi Kenmochi; Tomohisa Egawa; Shinobu Hayashi; Atsushi Nagashima; Yuko Kitagawa (Gastroenterology Research and Practice)
Background and Aim. Distal cholangiocarcinoma associated with choledocholithiasis has not been reported, and the causal relationship remains to be established. We evaluated diagnosis of distal cholangiocarcinoma diagnosed after the removal of choledocholithiasis. Patients and Methods. We assigned 9 cases of cholangiocarcinoma with choledocholithiasis to Group A. As a control group, 37 patients with cholangiocarcinoma without choledocholithiasis were assigned to Group B. Results. Abdominal pain at admission is the only significant difference between Group A and Group B (P=0.001). All patients in Group A had gall bladder stones, compared with 7 patients (19%) in Group B (P<0.01). Of the 9 patients in Group A, endoscopic retrade cholangiopancreatography (ERCP) detected normality in 2 patients (22%) and abnormalities in 7 patients (78%). Of the 32 patients in Group B, ERCP detected normality in 4 patients (13%) and abnormalities in 28 patients (88%) (P=0.597). Intraductal ultrasonography (IDUS) detected a tumor in 8 patients in Group A, while in Group B, IDUS detected normality in 1 patient (3%) and tumors in 29 patients (97%) (P=1.000). Conclusions. IDUS after stone removal may potentially help in the detection of unexpected tumors. Therefore, we believe that IDUS after stone removal will lead to improve outcome and prognosis.